2016
DOI: 10.1016/j.bbamem.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-mediated variations in cellular membrane fatty acid composition of Staphylococcus aureus in resistance to pulsed electric fields

Abstract: Effects of growth temperature on cell membrane fatty acid composition, fluidity and lethal and sublethal injury by pulsed electric fields (PEF) in Staphylococcus aureus ATCC 43300 (S. aureus) in the stationary phase were investigated. Analysis of the membrane fatty acids by gas chromatography-mass spectrometry (GC-MS) revealed that branched chain fatty acids (iso C14:0, iso C15:0, anteiso C15:0 and anteiso C17:0) and straight chain fatty acids (C12:0, C14:0, C16:0, C17:0 and C18:0) were primary constituents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 53 publications
1
28
0
2
Order By: Relevance
“…These observations revealed that EUG affected the morphology of E. coli cell membranes and PEF treatment resulted in damage to the integrity of E. coli cell membrane, which likely caused a decrease in reduction of log cycles of E. coli (Patrignani, Vannini, Kamdem, Lanciotti, & Guerzoni, ). These changes were similar to a previous study on inactivation of Staphylococcus aureus under PEF treatment (Wang, Wang, Zeng, & Liu, ), which showed PEF treatment could lead to structural changes of the microbiological cell membrane.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These observations revealed that EUG affected the morphology of E. coli cell membranes and PEF treatment resulted in damage to the integrity of E. coli cell membrane, which likely caused a decrease in reduction of log cycles of E. coli (Patrignani, Vannini, Kamdem, Lanciotti, & Guerzoni, ). These changes were similar to a previous study on inactivation of Staphylococcus aureus under PEF treatment (Wang, Wang, Zeng, & Liu, ), which showed PEF treatment could lead to structural changes of the microbiological cell membrane.…”
Section: Resultssupporting
confidence: 91%
“…Higher membrane fluidity was induced with an increase in EUG concentration, which likely reduced PEF resistance of E. coli cells. Previous studies have indicated that PEF inactivation could be enhanced due to an increase in membrane fluidity (Wang, Wang, Zeng, & Liu, 2016;Yun et al, 2017). Such changes of PEF resistance of E. coli were ascribed to the variations of membrane fluidity induced by the change in membrane fatty acid composition of E. coli at different EUG concentrations.…”
Section: As Indicated Inmentioning
confidence: 99%
“…The effect of growth temperature on fatty acid composition was well reported in many studies (e.g. Marr and Ingraham, 1962;Ray et al, 1971;Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, while 2D-TLC can provide accurate quantification of each lipid class, it requires large amounts of lipid extracts and does not provide specificity with regard to individual molecular species [14]. The application of targeted mass spectrometry methods has provided some insight into the chemical composition of specific S. aureus lipids [15,16], while gas chromatography mass spectrometry (GC-MS) has proved successful in determining the specific fatty acid composition of S. aureus following diverse genetic, chemical and environmental manipulations [17,18,19].…”
Section: Introductionmentioning
confidence: 99%